SAKRALITAS VIRTUAL: MAKNA SAKRAL DALAM IBADAH SALAT JUMAT VIRTUAL DI INDONESIA - Dede Syarif; Jajang A Rohmana; Qintannajmia Elvinaro (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2022)
This article discusses sacred experience in virtual worship. It focuses on virtual Friday prayer via zoom application leaded by Wawan Gunawan Abdul Wahid, scholar from Yogyakarta, which has been holding this ritual since the outbreak of COVID-19 pandemic. Using phenomenological approach, this research argues that congregation of virtual Friday prayers experience sacredness during the prayers through two conditionals: attachment and continuousness in a ritual. Devoutness in prayer emerges within engagement in a ritual. The sacred atmosphere ascends when the congregation of the virtual Friday prayer enter the virtual room for Friday prayer. This virtual Friday room demarcates an offline profane room from sacred virtual room for Friday prayer. In addition, the continually engagement in virtual Friday prayer contribute to devoutness and sacred feeling of the congregation. The engagement of the congregation stimulates collective bond among participant in virtual Friday prayers. Keywords: sacred, profane, virtual Friday prayer, worship, devoutness ABSTRAKArtikel ini membahas tentang pengalaman sakral dalam ibadah virtual. Fokus kajiannya adalah pada pelaksanaan salat Jumat virtual melalui aplikasi zoom dipimpin oleh Wawan Gunawan Abdul Wahid, seorang akademisi asal Yogyakarta, yang berlangsung sejak pandemi COVID-19. Melalui pendekatan fenomenologi, kajian ini berargumen bahwa para jamaah mendapatkan pengalaman sakral dalam pelaksanaan salat Jumat virtual. Pengalaman tersebut terbentuk melalui dua prasyarat: kebersamaan dan kesinambungan. Kekhusyukan itu timbul melalui kebersamaan sejak awal. Ketika semua jamaah memasuki ruang virtual zoom nuansa sakralitas mulai terasa. Di sini ruang virtual zoom menjadi pembatas antara ruang profan di alam nyata dengan ruang sakral di alam maya. Selain itu, perasaan kekhusyukan dan sakralitas itu juga tumbuh dan dikuatkan dengan kehadirannya pada salat Jumat virtual secara konsisten dan berkesinambungan. Jamaah yang selalu hadir secara tidak langsung menanamkan pada dirinya perasaan ikatan bersama dengan jamaah dan ibadah virtual tersebut. Kata Kunci: sakral, profan, Jumat virtual, ibadah, khusuk